SIMPLE ALCOHOL DRIVING TEST DEVICE AUTOMATION SCHEME - A.Xudayberdiyev; Sh. Baxriddinova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Efficient use of the proposed device in the laboratory, including the technology of alcohol production in the chemical and food industries, automatic control devices are of great importance in reducing the amount of heat consumed by polyethylene columns, speeding up the process of energy-saving and quality products.